2008
DOI: 10.1021/pr070496k
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of TRPC3-Interacting Proteins by Tandem Mass Spectrometry

Abstract: Mammalian transient receptor potential canonical (TRPC) channels are a family of nonspecific cation channels that are activated in response to stimulation of phospholipase C (PLC)-dependent hydrolysis of the membrane lipid phosphatidylinositol 4,5-bisphosphate. Despite extensive studies, the mechanism(s) involved in regulation of mammalian TRPC channels remains unknown. Presence of various protein-interacting domains in TRPC channels have led to the suggestion that they associate with proteins that are involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 42 publications
1
11
1
Order By: Relevance
“…Conclusive evidence for TRPC1 internalization by Arf6 was shown by the reduction in regulated trafficking of TRPC1 to the plasma membrane after store depletion. This finding is different from previous findings with TRPC3 and TRPC5 that are internalized via clathrin-dependent pathway [44,45]. The variations in channel internalization could be dictated by the variations in their regulatory mechanisms, e.g.…”
Section: Accepted Manuscriptcontrasting
confidence: 99%
“…Conclusive evidence for TRPC1 internalization by Arf6 was shown by the reduction in regulated trafficking of TRPC1 to the plasma membrane after store depletion. This finding is different from previous findings with TRPC3 and TRPC5 that are internalized via clathrin-dependent pathway [44,45]. The variations in channel internalization could be dictated by the variations in their regulatory mechanisms, e.g.…”
Section: Accepted Manuscriptcontrasting
confidence: 99%
“…17 Notably, the importance of TRPC3 in neuronal growth was recently emphasized also by a proteomic study that revealed a physical link between TRPC3 and proteins involved in neuronal growth. 18 A similar conclusion was reached for TRPC6 in a study that identified TRPC6 as molecular target of hyperforin, a bicyclic polyprenylated acylphloroglucinol derivate with antidepressive effects. Hyperforin was shown to induce neuronal axonal sprouting that was strictly TRPC6 dependent.…”
Section: Trpc3/6/7 and Neurological Disorderssupporting
confidence: 53%
“…32,[37][38][39][40] Biochemical evidence has also been provided for the association of G proteins, SERCA and PMCA as well as PLC with TRPC channels. It is interesting to note that TRPCs have the ability to interact with both plasma membrane as well ER-associated proteins (these have also been confirmed in proteomic studies for TRPC3 3,41 ). In addition, some TRPC proteins also bind lipids such as PIP 2 and possibly cholesterol.…”
mentioning
confidence: 66%